The Complete Letters of Henry James, 1884-1886 Volume 2. - James, Henry; Anesko, Michael; Zacharias, Greg W.; Sommer, Katie (Lincoln : Nebraska, 2021)
This fifteenth installment in the complete collection of Henry James's more than ten thousand letters records James's ongoing efforts to care for his sister, develop his work, strengthen his professional status, build friendships, and engage timely political and economic issues.
April 29 To Thomas Bailey Aldrich -- [May 1886] To Edmund Yates -- May 3 To Anne Benson Skepper Procter -- May 10 To Mary Morton Hartpence Sands -- May 13 To Mrs. Phelps -- May 16 To Lady Elizabeth Eberstadt Lewis -- May 19 To James Bryce -- May 19 To Henrietta Reubell -- May 19 To Laurence Alma-Tadema -- May 21 To Thomas Bailey Aldrich -- May 25 To Francis Boott -- May 27 To Thomas Bailey Aldrich -- May 29 To Mary James Wilkinson Mathews -- June 5 To Thomas Bailey Aldrich -- June 10 To Lady Isabella Augusta Persse Gregory -- June 10 To Miss Townley -- June 13 To Catharine Walsh
Description based upon print version of record.
June 13 To William James.
JSTOR
Keywords: James, Henry, -- 1843-1916 -- Correspondence; James, Henry, -- 1843-1916; Authors, American -- 20th century -- Correspondence; Authors, American -- 19th century -- Correspondence; Écrivains américains -- 20e siècle -- Correspondance; Écrivains américains -- 19e siècle -- Correspondance; Authors, American; 1800-1999; Personal correspondence